Antimicrobial resistance and species composition of Enterococcus spp. isolated from waters and sands of marine recreational beaches in Southeastern Brazil - Fernandes Cardoso de Oliveira, Ana Julia [UNESP]; Watanabe Pinhata, Juliana Maira [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Density, species composition and antimicrobial resistance in bacteria of the Enterococcus genus were evaluated in seawater and sands from 2 marine recreational beaches with different levels of pollution. The 2 beaches showed predominance of Enterococcus faecalis and Enterococcus faecium, in the water and the sand. Dry sand presented higher densities of Enterococcus sp. and higher frequency of resistant strains than wet sand and seawater. The beach with a higher degree of pollution presented higher percentages of resistant strains (66.7% and 61.5%, in sand and in water, respectively) and resistance to a larger number of antimicrobials compared with the less polluted beach, Ilha Porchat (35.7% and 31.25% of resistant strains in sand and water, respectively). in water samples, the highest frequencies of resistance were obtained against streptomycin (38.5%) and erythromycin (25%), whilst in sand, the highest frequencies were observed in relation to erythromycin and tetracycline (38.1% and 14.3%, respectively). These results show that water and sands from beaches with high indexes of faecal contamination of human origin may be potential sources of contamination by pathogens and contribute to the dissemination of bacterial resistance. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Enterococcus; antimicrobial resistance; marine water; sand beach